The start of a conversation on the value of New Zealand's human capital - Suzy Morrissey (New Zealand Government, The Treasury, 2018)
This paper starts a conversation on the value of New Zealand's human capital stock. It adopts a definition of human capital as "an individual's skills, knowledge, mental and physical health that enable them to participate fully in work, study, recreation, and in society more broadly".
Keywords: 330